Mutations in the gene coding for Escherichia coli DNA topoisomerase I affect transcription and transposition. - Sternglanz, R (1981)
Mutations in top, the structural gene for Escherichia coli DNA topoisomerase I, have been identified and mapped at 28 min on the chromosome, near cysB. Strains carrying deletions of the top gene are viable. The top mutations, however, do exert pleiotropic effects on transcription and transposition. Mutants lacking DNA topoisomerase I have a more rapid rate of induction and a higher level of catabolite-sensitive enzymes including tryptophanase and beta-galactosidase. This general activation of transcription by top mutations can be attributed to an increase in the negative superhelicity of the DNA in vivo when the topoisomerase activity is abolished. The frequency of transposition of Tn5, a transposon carrying kanamycin resistance, is decreased by a factor of 40 or more in top mutants. A direct or indirect role of the topoisomerase in transposition is discussed. The transposition frequency of Tn3, however, is not dependent on top. Based on the studies of the E. coli top mutants, it appears that the supX gene, which was originally studied in Salmonella typhimurium [Dubnau, E. & Margolin, P. (1972) Mol. Gen. Genet. 117, 91-112] is likely to be the structural gene for DNA topoisomerase I.